Antimicrobial factors in African multipurpose trees - El-Hassan, S.M.; Lahlou-Kassi, A.; Newbold, C.J.; Wallace, R.J. (International Livestock Research Institute, 1995)
Samples and extracts of foliage from African multipurpose trees (MPT) were screened for their effects on rumen protozoa and bacteria. The MPT species tested were Acacia aneura, Acacia angustissima, Chamaecytisus palmensis, Brachychiton populneum, Flindersia maculosa, Sesbania sesban, Leucaena leucocephala and Vernonia amyedalina. S. sesban was highly toxic to rumen protozoa from sheep reared in Aberdeen. The toxic factor was associated with the saponin-containing fraction of the plant. S. sesban may therefore be useful in suppressing protozoa and thereby improving protein flow from the rumen; however, protozoa from the rumen of sheep raised in Ethiopia were resistant to S. sesban, indicating that resistance, either endogenous or acquired, may be a problem in exploiting this antiprotozoal effect. The Acacia species were toxic to rumen bacteria, particularly the cellulolytic species of Ruminococcus. The cause of this toxicity was not identified.